Relatório final do estágio curricular obrigatório do curso de Medicina Veterinária: cardiomiopatia de fenótipo hipertrófico secundário ao hipertireoidismo em gato: relato de caso. - Menezes, Luciana de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O estágio curricular em prática veterinária foi realizado junto ao Hospital Veterinário da faculdade de Medicina Veterinária da USP campus de São Paulo, e ao Hospital Veterinário da Faculdade de Medicina Veterinária e Zootecnia campus de Botucatu e ao Hospital Veterinário Veros, São Paulo. A acadêmica acompanhou a rotina do setor de Clínica Médica de Pequenos Animais e Anestesiologia Veterinária, incluindo o atendimento clínico e procedimentos ambulatoriais e a realização das sedações, medicações pré-anestésicas, induções anestésicas, técnicas de anestesia locorregionais e procedimentos de anestesia geral inalatória. Ademais, neste presente trabalho, é relatado um caso de interesse: uma felina, fêmea, SRD, 9 anos de idade, portador de hipertireoidismo, apresentando sinais de cardiomiopatia de fenótipo hipertrófico. Após a avaliação pelo ecocardiograma foi notada a presença de efusão pleural, sendo indicado o procedimento de drenagem do líquido torácico e posteriormentefoi diagnosticado hipertireoidismo, justificando o quadro de cardiopatia.

The curricular internship in veterinary practice was carried out at the Veterinary Hospital of the Faculty of Veterinary Medicine at USP on the São Paulo campus, and at the Veterinary Hospital of the Faculty of Veterinary Medicine and Animal Science on the Botucatu campus and at the Veros Veterinary Hospital, São Paulo. The academic followed the routine of the Small Animal Medical Clinic and Veterinary Anesthesiology sector, including clinical care and outpatient procedures and the performance of sedation, pre-anesthetic medications, anesthetic inductions, locoregional anesthesia techniques and general inhalation anesthesia procedures. Furthermore, in this present work, a case of interest is reported: a feline, female, SRD, 9 years old, with hyperthyroidism, showing signs of cardiomyopathy with a hypertrophic phenotype. After evaluation by echocardiogram, the presence of pleural effusion was noted, and the thoracic fluid drainage procedure was indicated and hyperthyroidism was subsequently diagnosed, justifying the condition of heart disease
CURRICULAR INTERNSHIP FINAL REPORT MANDATORY VETERINARY MEDICINE COURSE Case of interest: Hypertrophic phenotype cardiomyopathy secondary to hyperthyroidism in a cat: case report
Keywords: Cardiomiopatias; Hipotireoidismo; Gato